Characterize the main adverse events with harm reported in a Teaching Hospital in Minas Gerais - Senne, Eva Claudia Venancio de; Paiva, Luciana; Peixoto, Patrícia Borges; Barros, Joyce Assunção; Zullo, Sergio Antonio; Oliveira, Cristina da Cunha Hueb Barata de (Revista de Epidemiologia e Controle de Infecção, 2021)
Background and Objectives: adverse events are a major public health problem. The purpose of the study was to characterize the main adverse events with harm reported in a teaching hospital in Minas Gerais. Methods: this is a retrospective cross-sectional descriptive study with quantitative approach, which assessed the reports on adverse events, carried out between January 2015 and December 2018. Pearson’s chi-square test was applied in order to verify the association between categorical variables. Cramer’s measure V was calculated to assess the degree of association between the respective variables. In the observation of statistically significant results, the Z test was applied to compare proportions with adjustments by the Bonferroni method. Results: a total of 445 adverse events were reported, being the highest number in 2018 (61.8%) involving “Abrasion and friction” process (44.7%), which correspond to grades 3 and 4 pressure injuries. Most adverse events were reported by the Emergency Unit (29.2%), and serious harm (7.6%) and deaths (1.3%) were more prevalent in this place. There was a statistically significant association between types of harm and types of incidents (p